"Nothing Is Expensive, Everything Cheap, Nothing Explosive!": Side Stories from Molenbeek, Brussels. Issue 1 (1st June 2020) - Moderbacher, Christine
Abstract: More than a year after the Brussels district Molenbeek came to international attention as "ISIS's European capital, " an unplanned encounter during a visit at my former field site leads to a conversation about the struggles and concerns that people are facing in this much-talked-about place. The discussion on a small restaurant terrace wanders off into disappointments and adjustments during research and life and is marked by a shared feeling of uncertainty that mirrors the atmosphere of a city that has seldom been portrayed beyond ephemeral media descriptions.